Developments in the field of allergy in 2016 through the eyes of Clinical and Experimental Allergy. Issue 12 (20th November 2017) - Roberts, G.; Boyle, R.; Crane, J.; Hogan, S. P.; Saglani, S.; Wickman, M.; Woodfolk, J. A.
Summary: In this article, we described the development in the field of allergy as described by Clinical and Experimental Allergy in 2016. Experimental models of allergic disease, basic mechanisms, clinical mechanisms, allergens, asthma and rhinitis, and clinical allergy are all covered.